Integrated national approaches to international operations: The cases of Denmark, UK, and the Netherlands - Finn Stepputat (Danish Institute for International Studies (DIIS), 2009)
As part of a larger study of how to improve Danish concerted civil and military planning and action, this sub-report looks at the national approaches of Denmark, the Netherlands and the UK. On the basis of available documents and interviews, the report analyzes the concepts, policies and structures that each has developed, as well as the drivers of and the problems with the processes involved.
Keywords: 300; Friedenssicherung; Internationale Truppe; Katastrophenhilfe; Strategie; Dänemark; Großbritannien; Niederlande; Afghanistan